"Anterolateral" approach to the hip: a systematic review of the correct definition of terms. Issue 2 (December 2020) - Lepri, Andrea Cozzi; Villano, Marco; Matassi, Fabrizio; Carulli, Christian; Innocenti, Massimo; Civinini, Roberto
Purpose: The Watson-Jones interval plane between tensor fascia lata (TFL) and the gluteus medius (GM) has come back into fashion in the past few years - Röttinger described the anterolateral minimal invasive approach (ALMI) for use in total hip replacement, in which the standard Watson-Jones interval was used, but with a completely intermuscular plane. However, the term anterolateral is often still utilised to describe intramuscular approaches in which the GM was violated, thus creating a potential misunderstanding in the literature. Accordingly, we have designed a study to answer the following questions: (1) are there articles in the recent literature that use the term "anterolateral" to describe different approaches; (2) which would be the correct description of the anterolateral approach? Methods: We did a systematic review of the literature based on PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines, to look for peer reviewed papers of any evidence level focusing on the definition of anterolateral approach; MEDLINE and EMBASE were searched. Results: 73 manuscripts met the criteria of the systematic search. 53 papers (72.6%) reported the term anterolateral approach to describe a complete intermuscular approach between the interval between GM and TFL. Nonetheless, in the remaining 20 papers (27.4%) the term anterolateral was used to describe intramuscular approaches in which the gluteus medius was violated. Conclusion: In about 1 out of 4 papers in the recent literature, the term anterolateral was utilised to describe approaches that are completely different both in terms of anatomy and function.